An Experimental Study on Characteristics of Condensation Lid for Thermosyphon-type Solar Energy Ethanol Distillation Tank on Distillation Performance - Klongdee, Harid; Jareanjit, Jaruwat (Recent Science and Technology, 2023)
This research study examined the condensation cap characteristics of the ethanol distillation performance using solar radiation as a heat source and a passive greenhouse drying cabinet enclosed by a 17-degree tilting glass sheet. Size 1.25 × 1.8 × 1 m3 joined with a flat plate solar collector size 0.75 × 1.35 m3 as a heat source to boil the volatile low-concentration ethanol solution through condensation to get a higher concentration. Ethanol solution at the initial concentration of 10% v/v and a volume of 10 liters was used. There were 3 cases in all experiments: Case 1, an inverted funnel cap distillation tank, where the ethanol solution was directly passed through a flat plate solar collector and condensed through a copper pipe outside the incubator. Case 2, a distillation tank with a conical lid facing up and condensed water is constantly circulating on the lid of the tank. Case 3, a distillation tank with a conical lid of a conical distillation tank has condensed water circulating on the lid of the tank at intervals. At 30 minutes/time, the average solar radiation on the day of the experiment was 18.30 MJ/m2/day. The results showed that in Case 1, the distillation capacity could produce 1.51 liters of ethanol/day at a concentration of 30% v/v. For Case 2, the distillation capacity can produce 3.02 liters of ethanol/day at a concentration of 39% v/v and in Case 3, distillation capacity can produce ethanol 3.37 liters/day at a concentration of 41% v/v from the test found. From the experiment in Case 3, it was found that the lid of the conical distillation tank had condensed water swirling on the lid of the tank at intervals of 30 min/time, resulting in the condensed water having no rotation to exchange heat with the ethanol solution in the distillation tank all the time. The experiments were conducted to achieve the highest water density at low temperatures with the highest sedimentation efficiency. The order of performance, from highest to lowest, is as follows: Case 3, followed by Case 2, and then Case 1.